2022
DOI: 10.29244/jtcs.9.01.8-14
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality of Guava (Psidium guajava ‘Kristal’) under Different Fruit Bagging Treatments and Altitudes of Growing Location

Abstract: Fruit quality is an important aspect that requires attention and more study when it comes to commercializing tropical fruits, including guava ‘Kristal’. This study aimed to evaluate the effect of bagging treatment and altitude of growing orchard on fruit quality of guava (Psidium guajava var. ‘Kristal’). This study was conducted at two local orchards managed by small-scale farmers, at Gunung Batu (1000 meters above sea level, m asl) and Brajaselebah (25 m asl), Lampung Province, Indonesia. A nested design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study indicates that the ideal growing place for salak plants is between 450 m to 650 m asl (Tabel 9). This study is in line with several previous studies which explained that altitude affects the flowering process and fruit enlargement (Sophie at al., 2017;Spinardi et al, 2019;Widyastuti et al, 2022). The soil analysis results showed that the total N and P2O5 contents at three locations in Tabanan were very low to low, while the K2O content at the six study sites was very low (Table 3).…”
Section: Quality Characteristics Of Salak Varietiesmentioning
confidence: 91%
See 1 more Smart Citation
“…This study indicates that the ideal growing place for salak plants is between 450 m to 650 m asl (Tabel 9). This study is in line with several previous studies which explained that altitude affects the flowering process and fruit enlargement (Sophie at al., 2017;Spinardi et al, 2019;Widyastuti et al, 2022). The soil analysis results showed that the total N and P2O5 contents at three locations in Tabanan were very low to low, while the K2O content at the six study sites was very low (Table 3).…”
Section: Quality Characteristics Of Salak Varietiesmentioning
confidence: 91%
“…Therefore, one way of handling salak quality is by undertaking severe studies for factors such as land and climate and adjusting agricultural patterns according to local climate conditions (Nassar et al, 2018). The success of each species to occupy the environment of an area is influenced by its ability to adapt optimally to all physical environmental factors (temperature, light, soil structure, humidity), biotic factors (interaction between species, competition, parasitism), and chemical factors including the availability of water, oxygen, pH, and nutrients (Nassar et al, 2018;Widyastuti et al, 2022). Moreover, a broad genetic variability would lead to wide phenotypic variability due to the effect of genetic-environment interaction (Ritonga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one way of handling salak quality is by undertaking severe studies for factors such as land and climate and adjusting agricultural patterns according to local climate conditions (Nassar et al, 2018). The success of each species to occupy the environment of an area is influenced by its ability to adapt optimally to all physical environmental factors (temperature, light, soil structure, humidity), biotic factors (interaction between species, competition, parasitism), and chemical factors including the availability of water, oxygen, pH, and nutrients (Nassar et al, 2018;Widyastuti et al, 2022). Moreover, a broad genetic variability would lead to wide phenotypic variability due to the effect of genetic-environment interaction (Ritonga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural techniques that have been studied to increase production and fruit quality include fruit bagging (Widyastuti et al 2022a), organic fertilizer application (Trivedi et al 2012;Goswami et al 2015), biofertilizer usage (Shukla et al 2014;Widyastuti et al 2021), flower bud thinning (Suman and Bhatnagar 2019), strangulation (Widyastuti et al 2019b), pruning (Bhagawati et al 2015;Lal et al 2016;Susanto et al 2019;Widyastuti et al 2019c), and the application of growth retardant (Lizawati 2008). Paclobutrazol is a growth retardant that triggers reproductive responses, particularly flowering initiation.…”
Section: Introductionmentioning
confidence: 99%